Teaching Strategies for Developing Islamic Character in Children: A Case Study of Tadika Al-Fikh Orchard, Pulau Pinang" - Ariani, Rini; Qorib, Muhammad; Zuliana, Zuliana (Journal of English Language and Education, 2025)
This study explores how Islamic values are taught and internalized by children at Tadika Al-Fikh Orchard Pulau Pinang. Considering the developmental stage of children who are still closely related to the world of fairy tales, this study also examines the impact of intensive Islamic character teaching on the formation of their religious character. Using a qualitative approach, data were collected through observation, interviews, and documentation, and their validity was tested using triangulation techniques. The results of the analysis show that the Islamic character teaching strategy at Tadika Al-Fikh Orchard Pulau Pinang is implemented through systematic planning, organizing, delivering, and managing stages. There are six main factors that influence the implementation of this strategy, namely child development, basic competencies to be achieved, availability of relevant teaching materials, proportional time allocation, completeness of learning facilities, and teacher abilities and competencies. These findings provide comprehensive insights into the implementation of Islamic character teaching and emphasize that the right strategy and in-depth understanding of the factors that influence the learning process are very important in forming a strong understanding of religion in children.